2022
DOI: 10.54099/ijibmr.v2i1.133
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Corporate Action Announcement and Market Reaction

Abstract: This study aims to determine the effect of market reaction in corporate action announcements on stock prices and stock liquidity. This study uses qualitative methods and literature research with reference to the latest journals published by scholars and examines literature books based on the theories discussed, especially in the context of financial management. The results of this study will build a research hypothesis which will be developed in further research by the author. The findings of this study will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Furthermore, the research by Handayani & Elmi (2023) states that effective communication is the key to forming a solid team, with emotional closeness playing a crucial role for women's teams. Overall, this research emphasizes that core values play a key role in guiding harmonious behavior among team members, contributing effectively to the achievement of organizational goals (Liyas & Adrianto, 2022;Ulfa & Salim, 2022). Previous research results show a gap where current research on "AKHLAK" is still conducted quantitatively.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, the research by Handayani & Elmi (2023) states that effective communication is the key to forming a solid team, with emotional closeness playing a crucial role for women's teams. Overall, this research emphasizes that core values play a key role in guiding harmonious behavior among team members, contributing effectively to the achievement of organizational goals (Liyas & Adrianto, 2022;Ulfa & Salim, 2022). Previous research results show a gap where current research on "AKHLAK" is still conducted quantitatively.…”
Section: Introductionmentioning
confidence: 86%
“…Since 2022, the company has mandated all employees to participate in and complete e-learning training aimed at introducing and developing "AKHLAK" values. The focus of this training is the development of employees' soft skills by introducing and instilling key points of "AKHLAK" culture as fundamental competencies implemented in their daily work environment (Iskamto, 2012(Iskamto, , 2023Jatmiko, 2022;Liyas & Adrianto, 2022;Rudianto et al, 2022). In this research, through interviews and initial observations of several informants, it was found that employees in the company are aware of the importance of "AKHLAK" culture but have not yet felt the direct impact of its implementation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The capital market also has the potential to serve as an intermediary institution. Because the capital market is able to connect parties in need of funds with parties in possession of excess funds, this function demonstrates the significant role that the capital market plays in sustaining the economy (Iskamto, Ghazali, and Afthanorhan 2020;Kamaruddin, Wahyudi, and Gani 2022;Liyas and Adrianto 2022;Rudianto et al 2022;Sunaryo 2022;Ulfa and Salim 2022). Additionally, parties who are overfunded (investors) have access to the capital market, which enables them to select investment alternatives that offer the highest possible returns.…”
Section: Literature Reviewmentioning
confidence: 99%